Internalizing problems: review of interventions on Parental practices (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Despite the association between internalizing problems and family variables, interventions that focused exclusively on children and adolescents domains still predominate. This study aimed to identify and describe characteristics of intervention programs for internalizing problems which include children, adolescents and parents. Different keywords were combined in the CAPES search website. There were found five international intervention studies, which were assessed entirely and described on the design, participants, content and characteristics of interventions, outcomes, and follow-up. The effectiveness of parent interventions was discussed according to the consistency of the procedures content with risk and protective factors described in the literature.
Keywords: Internalizing problems; parenting; intervention